2014
DOI: 10.1111/jcmm.12315
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that the population of quiescent bone marrow‐residing very small embryonic/epiblast‐like stem cells (VSELs) expands in response to neurotoxic treatment

Abstract: The concept that bone marrow (BM)-derived cells may participate in neural regeneration remains controversial, and the identity of the specific cell type(s) involved remains unknown. We recently reported that the adult murine BM contains a highly mobile population of Sca-1+Lin−CD45− cells known as very small embryonic/epiblast-like stem cells (VSELs) that express several markers of pluripotency such as Oct-4. In the BM microenvironment, these cells are kept quiescent because of epigenetic modification of certai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 42 publications
1
17
1
Order By: Relevance
“…This observation laid the foundation for the concept that G-CSF mobilization can be employed to harvest these cells from patients for therapeutic purposes in regenerative medicine. Several reports also provided evidence that VSELs are mobilized into PB during strenuous exercise, infections, and sepsis as well as in patients suffering from heart infarct, stroke, skin burns, active inflammatory bowel disease, and several types of cancer [83][84][85][86][87][88][89][90][91] More importantly, based on our preliminary data, we also envision that in several clinical situations the number of VSELs circulating in PB in patients could be of prognostic value. This possibility, however, requires further study and long-term clinical correlations.…”
Section: Mobilization Of Vsels Into Pb In Response To Stress and Tissmentioning
confidence: 85%
“…This observation laid the foundation for the concept that G-CSF mobilization can be employed to harvest these cells from patients for therapeutic purposes in regenerative medicine. Several reports also provided evidence that VSELs are mobilized into PB during strenuous exercise, infections, and sepsis as well as in patients suffering from heart infarct, stroke, skin burns, active inflammatory bowel disease, and several types of cancer [83][84][85][86][87][88][89][90][91] More importantly, based on our preliminary data, we also envision that in several clinical situations the number of VSELs circulating in PB in patients could be of prognostic value. This possibility, however, requires further study and long-term clinical correlations.…”
Section: Mobilization Of Vsels Into Pb In Response To Stress and Tissmentioning
confidence: 85%
“…VSELs can differentiate into neurons, oligodendrocytes, and microglia (Havens et al, 2014). Their potential for neurogenesis thus makes them valuable candidates for stroke therapy (Grymula et al, 2014). However, transplantation studies are limited by the extremely low yield of VSELs that can be viably obtained by current harvesting protocols (Shin et al 2013).…”
Section: Identifying the Optimal Cell Type For Stem Cell Transplanmentioning
confidence: 99%
“…As mentioned above, G-CSF encourages VSEL mobilization, but chronic increases in plasma-circulating IGF-1 may actually accelerate the depletion of VSEL stores in adult tissues (Kucia et al, 2008; Kucia et al, 2013). Additionally, in an animal model of toxic brain damage induced via the administration of kainic acid, it was demonstrated that not only do VSELs mobilize following the neurotoxic insult but also the bone marrow pool of quiescent VSELs undergoes expansion, suggesting the endogenous proliferation of VSEL stores may occur (Grymula et al, 2014). Evidence of VSELs being mobilized into circulation after injury suggest that these cells may play a role in the mediation of injury-induced damage, including the sequestration of neuroinflammation.…”
Section: Identifying the Optimal Cell Type For Stem Cell Transplanmentioning
confidence: 99%
“…were injected daily with 1 mg of BrdU solution to evaluate whether SexHs affect proliferation of stem cells, and the final injection of BrdU was performed 1 h before sacrificing the animals [20]. MNCs were subsequently isolated from BM after lysis of erythrocytes and immunostained for expression of Sca-1, CD45, and Lin markers, as previously reported [19], as well as for the presence of BrdU (FITC BrdU Flow Kit; BD Pharmingen).…”
Section: In Vivo Brdu Treatmentmentioning
confidence: 99%